The formative evaluation of a HIV/AIDS module for first-year teacher education students at the Central University of Technology, Free State - Nel, C. C. (University of the Free State, 2014)
This study presents the embodiment of an evaluation of a compulsory HIV and AIDS modular (pilot) training programme for first-year Teacher Education students at the CUT: FS. The study focussed extensively on the evaluation of the HIV/AIDS module content with comparative norms and dimensions identified from contemporary literature on HIV and AIDS. Living positively with HIV and AIDS was evaluated in terms of the following: • How to prevent the spread of the disease: bio-medical knowledge base • How to care and support people living with HIV and AIDS • How to handle grief caused by the deaths of loved ones, and • How to support orphans and vulnerable children. Data were obtained from a group of (n=90) Teacher Education students that completed the modular course during the latter part of 2011. An appropriate questionnaire covering the respective dimensions was completed by 90 out of 200 students under controlled conditions. The data collected were professionally analysed by the Department of Statistics at the University of the Free State. The results obtained provided sufficient information reflecting that the module was not successful in altering the respondents’ attitudes, knowledge or skills regarding people living with HIV/AIDS, or that the retention of what was learned was not lasting.

Afrikaans:Hierdie navorsingstuk vervat die evaluering van 'n verpligte MIV/Vigs modulêre opvoedkunde gidsprogram vir Eerstejaar Onderwysstudente aan die Sentale Universiteit van Tegnologie, Vrystaat (SUT). Die studie was hoofsaaklik gerig op die evaluering van die MIV/Vigs module inhoud met vergelykende norme en dimensies volgens hedendaagse MIV/Vigs literatuur. 'n Positiewe lewenswyse met MIV/Vigs word geëvalueer in terme van die volgende: • Hoe om die verspreiding van die siekte te beperk: biomediese kennis • Hoe om mense met met MIV/Vigs te ondersteun en te versorg • Hoe om te handel met die verdriet en hartseer wat veroorsaak word deur die afsterwe van geliefdes, en • Hoe om ondersteuning te bied aan wees- en kwesbare kinders Data is verkry vanaf 'n groep (n=90) Opvoedkunde onderrig studente wat die modulêre kursus gedurende laat 2011 voltooi het. 'n Toepaslike vraelys wat handel oor onderskeie dimensies is onder beheerde omstandighede afgeneem by 90 uit 'n moontlike 200 studente. Die data is professioneel verwerk deur die Universitet van die Vrystaat se Departement van Statistiek. Verwerfde resultate het genoegsame inligting verskaf om aan te toon dat die Module nie daarin kon slaag om die respondente se houding, kennis en vaardighede te bevorder rakende mense wat saamleef met MIV/Vigs nie, en/of dat die retensie vermoë van wat geleer is, nie langdurig van aard was nie.
Dissertation (M.Ed. (Higher Education Studies))--University of the Free State, 2014
Keywords: Devastating effects of the pandemic; Vulnerability of adolescents to infection; Escalation of the disease; HIV and AIDS prevalence and infection rates; Need to adapt a less risky lifestyle; Need to educate learners in order to advance their knowledge; Skills and behaviours towards living positively with HIV and AIDS; Teachers -- Training of; Curriculum planning; AIDS (Disease) -- Study and teaching; HIV infections -- Study and teaching